Respuesta :
(Edit: 34 is meant to be 3/4)
I hope I can help! :)
f(1/2) = -11/8
f(x) basically means y. So, you could translate it as
y= -3/4x + 1
(1/2) would equal (x) so the function would look like this:
f(1/2) = -3/4(1/2)+1
Here are the steps to solve:
1. Multiply -3/4(1/2)
-3/4(1/2) = -3/8
2. Add 1 to -3/8
1 + -3/8 = -1 3/8
3.Reduce -1 3/8
-1 3/8 = -11/8
f(1/2) = -11/8
---------------------------
Have a great day/evening/night! :)
Let me know if you have any additional questions!
-Kappifilms
I hope I can help! :)
f(1/2) = -11/8
f(x) basically means y. So, you could translate it as
y= -3/4x + 1
(1/2) would equal (x) so the function would look like this:
f(1/2) = -3/4(1/2)+1
Here are the steps to solve:
1. Multiply -3/4(1/2)
-3/4(1/2) = -3/8
2. Add 1 to -3/8
1 + -3/8 = -1 3/8
3.Reduce -1 3/8
-1 3/8 = -11/8
f(1/2) = -11/8
---------------------------
Have a great day/evening/night! :)
Let me know if you have any additional questions!
-Kappifilms